ChemRAP uncovers specific mRNA translation regulation via RNA 5′ phospho-methylation - Ipas, Hélène; Gouws, Ellen B; Abell, Nathan S; Chiou, Po-Chin; Devanathan, Sravan K; Hervé, Solène; Lee, Sidae; Mercado, Marvin; Reinsborough, Calder; Halabelian, Levon; Arrowsmith, Cheryl H; Xhemalçe, Blerta (EMBO reports, 2024)
5′-end modifications play key roles in determining RNA fates. Phospho-methylation is a noncanonical cap occurring on either 5′-PPP or 5′-P ends. We used ChemRAP, in which affinity purification of cellular proteins with chemically synthesized modified RNAs is coupled to quantitative proteomics, to identify 5′-Pme “readers”. We show that 5′-Pme is directly recognized by EPRS, the central subunit of the multisynthetase complex (MSC), through its linker domain, which has previously been involved in key noncanonical EPRS and MSC functions. We further determine that the 5′-Pme writer BCDIN3D regulates the binding of EPRS to specific mRNAs, either at coding regions rich in MSC codons, or around start codons. In the case of LRPPRC (leucine-rich pentatricopeptide repeat containing), a nuclear-encoded mitochondrial protein associated with the French Canadian Leigh syndrome, BCDIN3D deficiency abolishes binding of EPRS around its mRNA start codon, increases its translation but ultimately results in LRPPRC mislocalization. Overall, our results suggest that BCDIN3D may regulate the translation of specific mRNA via RNA-5′-Pme. Synopsis Affinity purification of cellular proteins with chemically modified RNAs coupled to quantitative proteomics is used to identify 5′-Pme “readers”. The identified binder of 5′-Pme and its writer potentially regulate the translation of specific mRNAs important for metabolism and mitochondrial function in human cells. ChemRAP identifies 5′-Pme non-canonical capping “reader” proteins EPRS binding to RNA is increased by 5′-Pme and occurs through its linker domain. Knockout of the BCDIN3D 5′-Pme writer in human cells abolishes binding of specific mRNAs to EPRS and increases aberrant translation initiation. Affinity purification of cellular proteins with chemically modified RNAs coupled to quantitative proteomics is used to identify 5′-Pme “readers”. The identified binder of 5′-Pme and its writer potentially regulate the translation of specific mRNAs important for metabolism and mitochondrial function in human cells.